2020
DOI: 10.1111/head.14028
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using “SMARTER” methodology for monitoring precipitating conditions of pediatric migraine episodes

Abstract: Objective: To evaluate the feasibility in children of an intensive prospective data monitoring methodology for identifying precipitating conditions for migraine occurrence. Background: Migraine headaches are a common pain condition in childhood and can become increasingly chronic and disabling with repeated episodes. Identifying conditions that forecast when a child's migraine is likely to occur may facilitate next-generation adaptive treatments to prevent future migraine attacks. Methods: In this cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Another example is a functional MRI study showing that the distance to the next headache attack is predictable by the signal intensities in the trigeminal spinal nuclei in the preictal phase (31). In addition, continuous data monitoring and sleep time data, as discussed above, also provides predictive value (23,24). While these biomarkers and physiological measurements are less accessible than simple self-reporting predictors; they suggest that we should look for a broad variety of biomarkers and phenotypic features to include in high-dimensional models forecasting migraine attacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is a functional MRI study showing that the distance to the next headache attack is predictable by the signal intensities in the trigeminal spinal nuclei in the preictal phase (31). In addition, continuous data monitoring and sleep time data, as discussed above, also provides predictive value (23,24). While these biomarkers and physiological measurements are less accessible than simple self-reporting predictors; they suggest that we should look for a broad variety of biomarkers and phenotypic features to include in high-dimensional models forecasting migraine attacks.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of using headache diary apps and wearable biosensors for headache prediction has also been demonstrated in several studies. In a study by Connelly and Boorigie (23) it was shown that children with migraine could use their smartphone to routinely report headaches and daily activities, while wearables could provide passive data monitoring for the majority of the day on most days. The authors conclude that such methods for data capture should be suited for machine learning analytics, and should indeed be considered when designing future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, biosensors directly favor the collection of information on objective health parameters of physiological states, such as in the study on predisposing factors for migraine in children, 11 control and monitoring of children with autism, 12 and even psychological conditions such as fatigue in high-load workers and the resulting loss of productivity, welfare, and safety. 13 …”
Section: Introductionmentioning
confidence: 99%